Training on antibacterial liquid soap making from nipah leaf extract to support SDGs-3 good health and well being - Yuanita Amalia Hariyanto; Aditya Lapu Kalua; Bukroanah Amir Makkau; Imam Jayanto (Community Empowerment, 2024)
Wori Village, located in the buffer zone of the Likupang Tourism Special Economic Zone (KEK), requires development of both its natural and human resources. Natural resource optimization can be achieved through diversification, specifically by producing liquid soap from the nipah plant. Human resource development necessitates increased public awareness of skin health and personal hygiene. This Community Service aimed to educate the Wori Village community on personal hygiene and provide a practical solution for reducing skin diseases through the use of antibacterial liquid soap. The methodology comprised socialization, training, technology application, mentoring, evaluation, and plans for program sustainability. The resulting NIPALS soap met quality standards, exhibiting a pH of 7. Evaluation demonstrated a 96.7% increase in participants' knowledge of personal hygiene and soap-making (pre-test vs. post-test). Furthermore, 95.5% of participants expressed satisfaction with the soap (4.5% considered it average). Positive user experiences included a 97% absence of itching, 76.7% reporting a tightening effect, and 70% noting moisturization. These results, supported by positive hedonic test results, confirm the successful production of liquid soap by the participants.